A study on the pattern of selfie culture among university students in Bangladesh - Mim, Moriom Begum; Asaduzzaman, ASM (Informasi, 2024)
This study endeavors to explore the determinants behind the prevalence of selfie culture in the light of self-presentation strategies. It applied Erving Goffman's (1959) Self-Presentation theory to scrutinize the pattern of selfie culture among university students in Bangladesh. Following a qualitative methodology, semi-structured interviews were conducted among 20 participants as a purposive sample age range from 20 to 25 years old. The results demonstrate that the participants tend to invest considerable attention to take selfies, afterward use filters to maximize the "best version" of the self, and eventually post them in the digital world. Their desire to represent the "best version" of themselves and gain the attention of others reflect the narcissist traits of the participants. Also, their level of self-esteem increases when they feel confident and see their "retouched image" after using photographic filters.